Alteration of IGFBP-1 in soccer players due to intensive training - Lagundzin, D.; Vucic, V.; Glibetic, M.; Nedic, O. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Physical activity is accompanied by the changes in Insulin-like Growth Factor I (IGF-I)/IGF-Binding Protein 1 (IGFBP-1) axis. Inconsistent results concerning IGF-I and IGFBP-1 levels were reported. In this study we have raised some questions on the events that occur at the molecular level of the exercise-related IGFBP-1 changes. We have examined the fragmentation pattern of IGFBP-1, IGFBP-1 protease activity, interaction between IGFBP-1 and alpha2-macroglobulin (?2M), and possible existence of minor structural changes of IGFBP-1 in professional soccer players. Athletes had significantly greater amounts of fragmented IGFBP-1, whereas no difference was found in the amount of intact IGFBP-1 compared with controls. An increased activity of matrix metalloprotease-9 (MMP-9) was detected in athletes, causing IGFBP-1 degradation down to the fragment of 9 kDa as the major one. The amount of Alpha2M, which protects IGFBP-1 from proteolysis, or the amount of IGFBP-1/Alpha2M complexes was unaltered. Finally, we have examined whether IGFBP-1 isolated from soccer players exhibited altered reactivity with several chemical surfaces used in surface-enhanced laser desorption/ionization-time of flight mass spectrometry (SELDI-TOF MS). Different reactivity was detected with anion and cation exchangers, suggesting existence of at least one sequence within IGFBP-1, whose ionization pattern was not equal in athletes and controls. Differences in spectra obtained with ion exchanges may reflect differences in IGFBP-1 phosphorylation. Physiological implications of the events described in this study on the IGF-I availability are, at this time, unknown. It can be hypothesized that IGFBP-1 proteolysis leads to altered distribution of IGF-I among IGFBPs, which may affect the final IGF-associated response.